Antimony-doped tin dioxide-vanadium dioxide composite film and preparation method thereof
By introducing antimony-doped tin dioxide film as an intermediate buffer layer on the building glass, the deposition temperature of the vanadium dioxide film is reduced, the problems of difficult preparation and high energy consumption in the prior art are solved, and low-cost and efficient heat is achieved Preparation of discoloration films.
Patent Information
- Application Number
- CN202411541337.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to prepare vanadium dioxide films with thermochromic properties at low cost and efficiently on building glass, mainly because magnetron sputtering equipment is difficult to achieve high substrate temperature, which increases the production difficulty and energy consumption.
By introducing an antimony-doped tin dioxide film as the intermediate buffer layer, the vanadium dioxide film is grown in situ on it, thereby reducing the deposition temperature of the vanadium dioxide film. The specific method includes growing a Sb2O3-doped SnO2 film on the amorphous substrate layer as an intermediate layer, and growing a vanadium dioxide film layer thereon by radio frequency magnetron sputtering, and the substrate temperature is controlled between 400°C and 450°C.
The deposition temperature of vanadium dioxide thin film is achieved, the preparation cost and energy consumption are reduced, while the semiconductor-metal transition effect and thermal discoloration effect of the film are maintained, and the phase transition temperature is also reduced.
Smart Images

Figure CN119411084A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thin film material preparation technology, and in particular relates to an antimony-doped tin dioxide-vanadium dioxide composite film and a preparation method thereof. Background Art
[0002] With the intensification of global warming, the increasing depletion of energy and the need for sustainable development, building energy conservation has become an important issue that needs to be solved urgently worldwide. Among them, glass doors and windows are the weak link in building energy conservation, and their energy loss accounts for more than 50% of building energy consumption. The main technical means of glass energy conservation is to prepare thin film structures on architectural glass to regulate the optical and thermal properties of glass.
[0003] At present, the commonly used energy-saving glass is silver-based low-emissivity glass with unadjustable energy-saving performance. People are more looking forward to a smart window glass that can dynamically adjust the transmittance and reflectivity of sunlight according to changes in the external environment. This is considered to be a technical means to effectively reduce building energy consumption.
[0004] As a thermochromic material, vanadium dioxide undergoes a reversible transition from a metallic state to a semiconductor state at a critical temperature, which is manifested in a huge difference in transmittance and resistivity in the near-infrared band before and after the phase transition. It can be used to intelligently control the optical and thermal properties of glass according to the ambient temperature. Magnetron sputtering is a common method for offline glass coating. The development of magnetron sputtering coating technology is necessary for the practical application of vanadium dioxide thin film-based smart windows.
[0005] Existing research results show that it is very difficult to prepare vanadium dioxide thin films with thermochromic properties directly on glass substrates using magnetron sputtering, and the substrate temperature is generally required to be above 550°C. However, it is difficult for magnetron sputtering equipment used for architectural glass coating to achieve a very high substrate temperature. In addition, high substrate temperature increases the cost of preparing thin films, increases the difficulty of preparation, and also leads to high energy consumption.
[0006] It has been reported that the deposition temperature of vanadium dioxide thin films can be reduced to a certain extent by introducing substrate bias, but large-area bias devices cannot be implemented in industrial magnetron sputtering equipment.
[0007] Therefore, how to significantly reduce the substrate temperature for vanadium dioxide film deposition is a difficult point in preparing vanadium dioxide films by magnetron sputtering. Summary of the invention
[0008] The present invention aims at the problems and shortcomings of the prior art, introduces an antimony-doped tin dioxide film as an intermediate buffer layer, and in-situ grows a vanadium dioxide film thereon, thereby reducing the deposition temperature when growing the vanadium dioxide film. The prepared antimony-doped tin dioxide-vanadium dioxide composite film has obvious semiconductor-metal transition effect and thermochromic effect.
[0009] To achieve the above-mentioned objects, the present disclosure includes the following inventions.
[0010] On the one hand, the present disclosure relates to an antimony-doped tin dioxide-vanadium dioxide composite film, which has an amorphous substrate layer, an antimony-doped tin dioxide intermediate layer and a vanadium dioxide film layer, wherein the antimony-doped tin dioxide intermediate layer is a SnO2 film doped with Sb2O3.
[0011] In the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, the doping amount of Sb2O3 in the Sb2O3-doped SnO2 film of the antimony-doped tin dioxide intermediate layer is preferably 1 to 5% in terms of atomic percentage.
[0012] In the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, the Sb2O3-doped SnO2 film of the aforementioned antimony-doped tin dioxide intermediate layer is preferably crystalline.
[0013] In the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, the aforementioned amorphous substrate layer is preferably quartz glass.
[0014] On the other hand, the present disclosure relates to a method for preparing the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, which comprises the following steps:
[0015] Antimony-doped tin dioxide intermediate layer growth process: using Sb2O3-doped SnO2 as a target material, a Sb2O3-doped SnO2 film is grown on an amorphous substrate layer at a substrate temperature of 400°C to 450°C by radio frequency magnetron sputtering to form an antimony-doped tin dioxide intermediate layer;
[0016] The vanadium dioxide film growth process is as follows: using a V2O3 ceramic target as a target material, a vanadium dioxide film is grown on the antimony-doped tin dioxide intermediate layer by adopting a radio frequency magnetron sputtering method at a substrate temperature of 400°C to 450°C.
[0017] In the aforementioned method for preparing the antimony-doped tin dioxide-vanadium dioxide composite film, preferably, after the aforementioned antimony-doped tin dioxide intermediate layer growth process and before the aforementioned vanadium dioxide film layer growth process, there is also a heat preservation process of keeping warm at a temperature of 400-450°C for 0.5-1 hour.
[0018] In the aforementioned method for preparing antimony-doped tin dioxide-vanadium dioxide composite film, preferably, in the aforementioned antimony-doped tin dioxide intermediate layer growth process, the inert gas flow rate used is 10-20 sccm, the oxygen flow rate is 0-0.2 sccm, the sputtering working gas pressure is 3-10 mTorr, the sputtering power of the target material is 80-100 W, and the sputtering time is 15 min-60 min.
[0019] In the aforementioned method for preparing the antimony-doped tin dioxide-vanadium dioxide composite film, preferably, in the aforementioned vanadium dioxide film layer growth step, sputtering is performed under the conditions of an inert gas flow rate of 10 to 20 sccm and an oxygen flow rate of 0.2 to 0.5 sccm.
[0020] In the aforementioned method for preparing antimony-doped tin dioxide-vanadium dioxide composite film, preferably, in the aforementioned vanadium dioxide film growth process, the sputtering working pressure is 3-10 mtorr, the sputtering power of the target material is 60-90 W, and the sputtering time is 100 min-150 min.
[0021] In the aforementioned method for preparing antimony-doped tin dioxide-vanadium dioxide composite film, preferably, in the aforementioned SnO2 doped with Sb2O3 as the target material, the doping amount of Sb2O3 in atomic percentage is 1-5%.
[0022] The antimony-doped tin dioxide-vanadium dioxide composite film disclosed in the present invention has obvious semiconductor-metal transition effect and thermochromic effect, and the phase transition temperature is reduced.
[0023] The method for preparing the antimony-doped tin dioxide-vanadium dioxide composite film disclosed in the present invention introduces the antimony-doped tin dioxide film as an intermediate buffer layer, and in-situ grows a vanadium dioxide film thereon, thereby reducing the deposition temperature when growing the vanadium dioxide film. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 Graph showing the transmittance of the antimony-doped tin dioxide-vanadium dioxide composite film prepared in Examples 1 to 4 before and after phase change.
[0026] Figure 2 Graph showing the transmittance of the antimony-doped tin dioxide-vanadium dioxide composite film prepared in Examples 5-6 before and after phase change.
[0027] Figure 3 The transmittance-temperature curves of the antimony-doped tin dioxide-vanadium dioxide composite films prepared in Example 1 and Examples 3-4 at 1550 nm are shown. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.
[0029] The present disclosure is further described in detail below in conjunction with the embodiments. It is to be understood that the described embodiments are only a part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.
[0030] [Antimony doped tin dioxide-vanadium dioxide composite film]
[0031] An antimony-doped tin dioxide-vanadium dioxide composite film according to one embodiment includes an amorphous base layer, an antimony-doped tin dioxide intermediate layer, and a vanadium dioxide film layer.
[0032] The antimony-doped tin dioxide-vanadium dioxide composite film disclosed in the present invention has good thermochromic properties, and the phase transition temperature of the vanadium dioxide film is reduced. Compared with the original phase transition temperature of vanadium dioxide of about 70 degrees, the phase transition temperature of the antimony-doped tin dioxide-vanadium dioxide composite film disclosed in the present invention can be reduced to, for example, a range of 50 to 60 degrees.
[0033] In the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, the aforementioned amorphous substrate layer is not particularly limited as long as it can serve as a substrate on which antimony-doped tin dioxide is generated, and can be, for example, a material that can withstand relatively high temperatures, such as ordinary architectural glass. From the perspective of high transparency, quartz glass is preferred.
[0034] In the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, the Sb2O3-doped SnO2 film of the aforementioned antimony-doped tin dioxide intermediate layer is required to have a high degree of crystallinity, and is therefore preferably crystalline.
[0035] In the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, the thickness of the aforementioned antimony-doped tin dioxide intermediate layer is not particularly limited, and may be, for example, 10 nm to 500 nm.
[0036] The aforementioned antimony-doped tin dioxide intermediate layer is a SnO2 film doped with Sb2O3. In the aforementioned Sb2O3-doped SnO2 film, preferably, the doping amount of Sb2O3 in atomic percentage is 1 to 5%. The aforementioned "doping amount in atomic percentage" is calculated as follows: for example, when the number of atoms of Sb in Sb2O3 contained in the Sb2O3-doped SnO2 film is set to a, and the number of atoms of Sn in SnO2 is set to b, the doping amount of Sb2O3 in atomic percentage is the value calculated by "a / (a+b)". By setting the doping amount of Sb2O3 in atomic percentage to more than 1%, a VO2 thin film with thermochromic properties can be grown using it as a buffer layer. In addition, from the perspective of obtaining a good SnO2 crystal structure and making it easier to grow a VO2 thin film, the doping amount of Sb2O3 in atomic percentage is set to less than 5%.
[0037] In the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film, the thickness of the aforementioned vanadium dioxide film layer is not particularly limited, and may be, for example, 10 nm to 200 nm.
[0038] According to needs, the vanadium dioxide film layer of the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film may also have a functional layer for realizing other functions, such as a layer of TiO2, ZnO, WO3, etc.
[0039] On the other hand, the method for preparing the aforementioned antimony-doped tin dioxide-vanadium dioxide composite film disclosed in the present invention comprises the following steps:
[0040] Antimony-doped tin dioxide intermediate layer growth process: using Sb2O3-doped SnO2 as a target material, a Sb2O3-doped SnO2 film is grown on an amorphous substrate layer at a substrate temperature of 400°C to 450°C by radio frequency magnetron sputtering to form an antimony-doped tin dioxide intermediate layer;
[0041] The vanadium dioxide film growth process is as follows: using a V2O3 ceramic target as a target material, a vanadium dioxide film is grown on the antimony-doped tin dioxide intermediate layer by adopting a radio frequency magnetron sputtering method at a substrate temperature of 400°C to 450°C.
[0042] It is very difficult to prepare a vanadium dioxide film with thermochromic properties directly on a substrate such as building glass by magnetron sputtering. The substrate temperature is generally required to be above 550°C, but it is difficult for the magnetron sputtering equipment used for coating building glass to achieve such a high substrate temperature. By adopting the aforementioned method for preparing an antimony-doped tin dioxide-vanadium dioxide composite film, an antimony-doped tin dioxide film is introduced between the amorphous substrate layer and the vanadium dioxide film layer as an intermediate buffer layer, thereby reducing the deposition temperature when growing the vanadium dioxide film. The inventors speculate that the reason may be that the lattice matching between vanadium dioxide and the antimony-doped tin dioxide film buffer layer is high and induces the growth of the vanadium dioxide film during the deposition process, thereby reducing its crystallization temperature.
[0043] [Antimony-doped SnO2 intermediate layer growth process]
[0044] By setting the substrate temperature in the aforementioned antimony-doped tin dioxide intermediate layer growth process to above 400°C, the effect of preparing a thermochromic VO2 thin film using it as a buffer layer can be obtained. On the other hand, in the RF magnetron sputtering method, the lower the substrate temperature, the lower the requirements on the material and other aspects of the RF magnetron sputtering device, which can reduce the cost of the device. From this aspect, the substrate temperature in the aforementioned antimony-doped tin dioxide intermediate layer growth process is more preferably 400°C to 420°C. The most preferred is 400°C.
[0045] The aforementioned antimony-doped tin dioxide intermediate layer growth process can be carried out under the following conditions: an inert gas flow rate of 10 to 20 sccm, an oxygen flow rate of 0 to 0.2 sccm, a sputtering working pressure of 3 to 10 mTorr, a target sputtering power of 80 to 100 W, and a sputtering time of 15 to 60 minutes. By introducing a small amount of oxygen, the oxygen content in the prepared Sb2O3-doped SnO2 film can be preserved, oxygen vacancies can be reduced, good crystallinity can be maintained, and the subsequent growth of VO2 thin film can be facilitated. From this point of view, the aforementioned oxygen flow rate is more preferably 0.05 to 0.2 sccm.
[0046] The inert gas used in the aforementioned antimony-doped tin dioxide intermediate layer growth step is argon.
[0047] In addition, in the aforementioned antimony-doped tin dioxide intermediate layer growth process, other conditions besides the various conditions of the RF magnetron sputtering method described above may adopt the conditions used in the conventional RF magnetron sputtering method, and those skilled in the art may appropriately determine them as needed without particular limitation.
[0048] [Vanadium dioxide film growth process]
[0049] In the aforementioned vanadium dioxide film growth process, when a V2O3 ceramic target is used as a target material, oxygen is contained in the atmosphere so that V2O3 is oxidized to obtain VO2 during the sputtering process. Preferably, in the aforementioned vanadium dioxide film growth process, sputtering is performed under the conditions of an inert gas flow rate of 10 to 20 sccm and an oxygen flow rate of 0.2 to 0.5 sccm. The inert gas serves as a sputtering gas and the oxygen serves as a reaction gas.
[0050] The inert gas used in the aforementioned vanadium dioxide film growth process is argon.
[0051] In the aforementioned method for preparing antimony-doped tin dioxide-vanadium dioxide composite film, preferably, in the aforementioned vanadium dioxide film growth process, the sputtering working pressure is 3-10 mtorr, the sputtering power of the target material is 60-90 W, and the sputtering time is 100 min-150 min.
[0052] In addition, in the aforementioned vanadium dioxide film growth process, other conditions besides the various conditions of the RF magnetron sputtering method described above may adopt the conditions used in the conventional RF magnetron sputtering method, and those skilled in the art may appropriately determine them as needed without any particular limitation.
[0053] [Heat preservation process]
[0054] In the aforementioned method for preparing the antimony-doped tin dioxide-vanadium dioxide composite film, preferably, after the antimony-doped tin dioxide intermediate layer growth process and before the vanadium dioxide film layer growth process, there is also a heat preservation process of keeping warm at a temperature of 400-450°C for 0.5-1 hour.
[0055] Through the aforementioned heat preservation process, the crystallinity of the antimony-doped tin dioxide film can be further improved, which is beneficial to the growth of the subsequent vanadium dioxide film layer.
[0056] In particular, when the sputtering time in the aforementioned antimony-doped tin dioxide intermediate layer growth process is relatively short, the crystallinity of the antimony-doped tin dioxide film formed on the amorphous substrate layer is not ideal and cannot effectively induce the growth of the thermochromic VO2 thin film. By having the aforementioned heat preservation process, the thermochromic performance of the subsequently grown vanadium dioxide film layer can be improved.
[0057] On the other hand, when the sputtering time in the aforementioned antimony-doped tin dioxide intermediate layer growth step is relatively long, the antimony-doped tin dioxide film formed during the sputtering process has sufficient crystallization time. In this case, the aforementioned heat preservation step may not be performed.
[0058] Example
[0059] In the following examples, the Sb2O3-doped SnO2 used as the target material was provided by Laiyan Technology, and the V2O3 ceramic was provided by Zhongnuo New Materials.
[0060] The mass purity of the argon gas used is 99.99%, and the mass purity of the antimony-doped tin dioxide target material and the V2O3 target material used are both 99.9%.
[0061] Example 1
[0062] First, the surface of the quartz glass substrate was cleaned with detergent, then rinsed with deionized water, and then ultrasonically cleaned with deionized water for 25 minutes, and then ultrasonically cleaned twice with anhydrous ethanol, each time for 50 minutes. After the ultrasonic cleaning is completed, the cleaned quartz glass sheet is immersed in anhydrous ethanol solution and sealed for standby use.
[0063] After the cleaned quartz glass sheet was blown dry, it was fixed on the sample stage of the magnetron sputtering instrument (Angstrom Engineering, NEXDEP-030). In addition, Sb2O3-doped SnO2 (the doping amount of Sb2O3 in terms of atomic percentage was 4%) and V2O3 were installed as targets. Then the chamber was closed and the vacuum degree of the chamber was evacuated to 5.0×10 -6 Torr, the substrate temperature is set to 400°C, the argon flow rate is controlled to be 15sccm, the sputtering working pressure is 4mTorr, and 0.2sccm of oxygen is introduced. The Sb2O3-doped SnO2 as the target material is sputtered at a sputtering power of 100W, wherein a 15min pre-sputtering (target cleaning) is first performed, and then a 60min sputtering is performed. After the sputtering is completed, a crystallized Sb2O3-doped SnO2 film is obtained as an antimony-doped tin dioxide intermediate layer.
[0064] Then, the chamber vacuum was maintained at 5.0×10 -6 Torr, 15sccm argon gas was introduced, the sputtering working pressure was 4mTorr, and 0.5sccm oxygen was introduced to sputter the V2O3 target, wherein the substrate temperature was 400°C, and a vanadium dioxide film was deposited on a crystallized antimony-doped tin dioxide film substrate. The sputtering power of the V2O3 target was 60W, and pre-sputtering (target cleaning) was performed for 15 minutes, and then sputtering was performed for 120 minutes to obtain a crystallized vanadium dioxide film.
[0065] Example 2
[0066] An antimony-doped tin dioxide-vanadium dioxide composite film was prepared in the same manner as in Example 1 except that the sputtering time of the Sb2O3-doped SnO2 film was changed to 30 min.
[0067] Example 3
[0068] The sputtering time of the Sb2O3-doped SnO2 film was changed to 30 minutes. In addition, after the formation of the antimony-doped tin dioxide intermediate layer, a heat preservation process was carried out at a substrate temperature of 400°C for 60 minutes, and then a subsequent vanadium dioxide film layer growth process was carried out. Other than this, the process was carried out in the same manner as in Example 1 to prepare an antimony-doped tin dioxide-vanadium dioxide composite film.
[0069] Example 4
[0070] The sputtering time of the Sb2O3-doped SnO2 film was changed to 15 minutes. In addition, after the formation of the antimony-doped tin dioxide intermediate layer, a heat preservation process was carried out at a substrate temperature of 400°C for 60 minutes, and then a subsequent vanadium dioxide film layer growth process was carried out. Other than this, the process was carried out in the same manner as in Example 1 to prepare an antimony-doped tin dioxide-vanadium dioxide composite film.
[0071] Example 5
[0072] An antimony-doped tin dioxide-vanadium dioxide composite film was prepared in the same manner as in Example 4 except that the doping amount of Sb2O3 in the Sb2O3-doped SnO2 used as the target material was changed to 1% by atomic percentage.
[0073] Example 6
[0074] An antimony-doped tin dioxide-vanadium dioxide composite film was prepared in the same manner as in Example 4 except that the deposition temperature of vanadium dioxide was changed to 450°C.
[0075] Comparative Example 1
[0076] The same procedure as in Example 1 was performed except that the antimony-doped tin dioxide intermediate layer growth step and the heat preservation step were not performed. As a result, a vanadium dioxide film could not be deposited on the quartz glass as the amorphous substrate. Therefore, for Comparative Example 1, the transmittance curve and the transmittance temperature curve described later were not measured.
[0077] For the antimony-doped tin dioxide-vanadium dioxide composite films prepared in Examples 1 to 4, the transmittance curves were measured at 20°C and 90°C in the range of 350 to 2500 nm. The results are shown in Figure 1 .from Figure 1 It can be seen that the antimony-doped tin dioxide-vanadium dioxide composite films prepared in Examples 1 to 4 have good thermochromic properties, among which the antimony-doped tin dioxide-vanadium dioxide composite film prepared in Example 4 has particularly excellent visible light transmittance and solar modulation efficiency. For the antimony-doped tin dioxide-vanadium dioxide composite films prepared in Examples 5 to 6, the transmittance curves were measured at 20°C and 90°C in the range of 350 to 2500nm, and the results are shown in Figure 2.from Figure 2 It can be observed that the antimony-doped tin dioxide-vanadium dioxide composite films prepared in Examples 5 to 6 also have good thermochromic properties.
[0078] For the antimony-doped tin dioxide-vanadium dioxide composite films prepared in Example 1 and Examples 3 to 6, the transmittance curves of the films at 1550 nm as a function of temperature were measured. The results are shown in Figure 3 .from Figure 3 It can be seen that the phase transition of the antimony-doped tin dioxide-vanadium dioxide composite film of Example 1 and Examples 3 to 6 mainly occurs in the range of 50 to 60° C., indicating that the preparation method disclosed in the present invention can effectively reduce the phase transition temperature of the vanadium dioxide film.
[0079] The present disclosure is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present disclosure, and these improvements and modifications are also considered to be within the scope of protection of the present disclosure. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
[0080] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An antimony-doped tin dioxide-vanadium dioxide composite film, characterized in that: The invention comprises an amorphous substrate layer, an antimony-doped tin dioxide intermediate layer and a vanadium dioxide film layer, wherein the antimony-doped tin dioxide intermediate layer is a SnO2 film doped with Sb2O3.
2. The antimony-doped tin dioxide-vanadium dioxide composite film according to claim 1, wherein: In the antimony-doped tin dioxide intermediate layer, the doping amount of Sb2O3 in atomic percentage is 1-5%.
3. The antimony-doped tin dioxide-vanadium dioxide composite film according to claim 1, wherein: The Sb2O3-doped SnO2 film of the antimony-doped tin dioxide intermediate layer is crystalline.
4. The antimony-doped tin dioxide-vanadium dioxide composite film according to claim 1, wherein: The amorphous substrate layer is quartz glass.
5. A method for preparing the antimony-doped tin dioxide-vanadium dioxide composite film according to any one of claims 1 to 4, comprising the following steps: Antimony-doped tin dioxide intermediate layer growth process: using Sb2O3-doped SnO2 as a target material, a Sb2O3-doped SnO2 film is grown on an amorphous substrate layer at a substrate temperature of 400°C to 450°C by radio frequency magnetron sputtering to form an antimony-doped tin dioxide intermediate layer; The vanadium dioxide film growth process is as follows: using V2O3 ceramic as a target material, a vanadium dioxide film is grown on the antimony-doped tin dioxide intermediate layer by radio frequency magnetron sputtering at a substrate temperature of 400°C to 450°C.
6. The method for preparing an antimony-doped tin dioxide-vanadium dioxide composite film according to claim 5 further comprises a heat preservation step of maintaining the temperature at 400 to 450° C. for 0.5 to 1 hour after the antimony-doped tin dioxide intermediate layer growth step and before the vanadium dioxide film layer growth step.
7. The method for preparing the antimony-doped tin dioxide-vanadium dioxide composite film according to claim 5, wherein: In the antimony-doped tin dioxide intermediate layer growth process, the inert gas flow rate is 10-20 sccm, the oxygen flow rate is 0-0.2 sccm, the sputtering working pressure is 3-10 mTorr, the sputtering power of the target material is 80-100 W, and the sputtering time is 15 min-60 min.
8. The method for preparing an antimony-doped tin dioxide-vanadium dioxide composite film according to claim 5, wherein: In the vanadium dioxide film growth process, sputtering is performed under the conditions of an inert gas flow rate of 10 to 20 sccm and an oxygen flow rate of 0.2 to 0.5 sccm.
9. The method for preparing an antimony-doped tin dioxide-vanadium dioxide composite film according to claim 5, wherein: In the vanadium dioxide film growth process, the sputtering working pressure is 3-10 mtorr, the sputtering power of the target material is 60-90 W, and the sputtering time is 100 min-150 min.
10. The method for preparing an antimony-doped tin dioxide-vanadium dioxide composite film according to claim 5, wherein: In the SnO2 doped with Sb2O3 as the target material, the doping amount of Sb2O3 in atomic percentage is 1-5%.
Citation Information
Cited By
Photo-thermal double-control type infrared stealth metamaterial and preparation method thereof
CN120575142A